Infra Patellar Branch of Saphenous Nerve Injury during Hamstring Graft Harvest: Vertical versus Oblique Incisions - Joshi, Amit; Kayasth, Nirab; Shrestha, Sailendra; KC, Bachchu Ram (Journal of Nepal Health Research Council, 2017)
Background: Autologous hamstring grafts are commonly used for anterior cruciate ligament reconstruction. The injury of infrapatellar branch of saphenous nerve is one of the concerns leading to various pattern of sensory loss in the operated leg. An oblique incision to harvest the graft has been reported to be better than the vertical one.The aim of this study was to compare the incidence, recovery of nerve injury and final outcome in patients with hamstring harvest of vertical or oblique incision. Methods: A total of 146 patients who underwent hamstring graft harvest for anterior cruciate ligament reconstruction, were included in the study. They were randomized into two (Vertical and Oblique) groups as per the incisions used. The sensory loss along the Infra Patellar Branch of Saphenous Nerve was documented on 3rd day. Recovery of the nerve injury was monitoredat three, six and 12 months follow-ups. At final follow up Tegner Lysholm score and scale was recorded to compare between two groups. Results: The incidence of infrapatellar branch of saphenous nerve injury was 25% in vertical group and 16.36% in oblique group. Recovery of nerve injury started earlier in oblique group compared to vertical group. The mean TegnerLyshom score was not significantly different in both the groups. Conclusions: Oblique incision to harvest hamstring graft has lesser incidence of infrapatellar branch of saphenous nerve injury, recovers earlier and does not have any adverse effect on final outcome compared to the vertical incision. Keywords: Anterior Cruciate Ligament; hamstring; harvest; infrapatellar branch; infra patellar branch of saphenous nerve.